Understanging consumer behaviours with in the scope of the covid-19 vaccine - GÜVEN, DENİZ (My University, 2021)
COVID-19 is one of the important crises which have threatened the social life. Recent news about the vaccine and mutation of the virus has led to a new uncertainty and rapid changes in the fear of COVID-19. In this new and uncertain process, a study on consumer behaviours within the framework of the COVID-19 vaccine is new and would contribute to the literature in the field. A factor analysis was made in order to understand the major effects of the vaccine on consumer behaviours. In the consequence of this study, which were conducted with the participation of 293 people living in Turkey, following the development of the vaccine, a significant relationship was detected between the realisation of the needs, purchase acts, information collection, option evaluation, compulsive purchase and post-purchase behaviour. The results obtained from the study were discussed within the framework of literature. Key words: Consumer Behaviour, Covid Fear, Vaccine
Keywords: Consumer Behaviour; Covid Fear; Vaccine